A historiographical perspective: Republican Italy, representation and gender representations (1945-1968) - Gabrielli, Patrizia (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
Historiography has examined suffrage and representation with originality and from different perspectives, but further elucidation can come from a study of the meanings that the “semiotic universe” of politics attributes to gender differences in public space. Based on research using press and archive sources, this article examines discursive practices in relation to “public man” and “public woman” in the first twenty years of Republican Italy. In order to highlight the many legacies of the past in Italian politics, I offer some insights into representations of “feminist” in the early twentieth century and “subversive” during the fascist regime.
Keywords: Italian Republic; historiography; gender; representative; representations